2004
DOI: 10.1590/s1517-86922004000600007
|View full text |Cite
|
Sign up to set email alerts
|

Déficit bilateral nos movimentos de flexão e extensão de perna e flexão do cotovelo

Abstract: Os exercícios resistidos (ER) podem ser realizados de forma uni e bilateral. O objetivo foi comparar a carga máxima (CM) na flexão e extensão de perna e flexão de cotovelo isoladamente e entre a soma desses dois resultados com aquele desenvolvido simultaneamente pelas duas pernas e dois braços, respectivamente. Foram submetidos 60 indivíduos ao exercício de flexão e extensão de perna e a flexão de cotovelo ao teste de 1RM. Os resultados para os movimentos de flexão e extensão de perna e flexão de cotovelo esqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
7
0
5
Order By: Relevance
“…This episode was probably reached by greater neural drive for the non-dominant limb, by the existence of possible deficiencies in the intermuscular coordination levels during movement, causing greater recruiting of motor units. Opposite data were found by Simão et al 9,10 and Chaves et al 11 , in which unilateral differences were not observed in load and maximum muscular power 6 . Some considerations must be mentioned concerning our findings.…”
Section: Contractionmentioning
confidence: 69%
See 1 more Smart Citation
“…This episode was probably reached by greater neural drive for the non-dominant limb, by the existence of possible deficiencies in the intermuscular coordination levels during movement, causing greater recruiting of motor units. Opposite data were found by Simão et al 9,10 and Chaves et al 11 , in which unilateral differences were not observed in load and maximum muscular power 6 . Some considerations must be mentioned concerning our findings.…”
Section: Contractionmentioning
confidence: 69%
“…When load, power and maximum repetitions until exhaustion are analyzed, Simão et al 9,10 and Chaves et al 11 verified the existence of bilateral deficit related to maximal load, but the same episode did not occur with maximal muscular power 9 . It is supposed that uni and bilateral maximal contractions are characterized concerning their neuromuscular activation, by the recruiting of many muscular groups or in many frequencies through a parallel process of intermuscular coordination.…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors, such difference called bilateral deficit, can be associated to the following aspects: reduced stimulation of motor units, neural recruiting differentiated by the crossed effect in the extra-pyramidal tract, fiber differences in the limbs, predominance of use of one limb over the other, resulting in a lower production of strenght (11)(12)(13) . Although the mechanisms responsible for the bilateral deficit are not very clear yet, it seems to be a consensus that the execution of the RE with simultaneous muscular actions tend to reduce the bilateral deficit, in relation to the work represented by the sum of the unilateral action of the strenght (10,14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…No estudo de Chaves et al 18 , foram encontrados resultados similares para o déficit bilateral em relação às cargas máximas para o movimento de extensão de joelhos, porém não foram evidenciados resultados significativos para o surgimento do déficit bilateral no movimento de flexão de joelhos realizado na cadeira flexora. Nossos achados reportaram que os indivíduos que realizaram reconstrução do LCA com autoenxerto dos músculos flexores do joelho, além de apresentarem o déficit bilateral, também possuem uma redução da força máxima no MO.…”
unclassified
“…Esse fato pode ter contribuído para as diferenças de força entre os membros encontradas nesse estudo. Dessa forma, a amostra selecionada pode ser uma das variáveis que justifica o déficit bilateral encontrado no movimento de flexão de joelhos e a diferença de força entre os membros, fato não reportado em estudos anteriores, realizados com indivíduos não operados 18 . O déficit de força bilateral também pode estar relacionado ao nível de condicionamento do indivíduo.…”
unclassified